Stock status and supporting species of anchovy fisheries in the northern of East Java, Indonesia - DEWA GEDE RAKA WIADNYA; LEDHYANE IKA HARLYAN; MUHAMMAD ARIF RAHMAN; SRI MARTA ISNAINIK MUSTIKARANI; EVI NUR SOKHIKHATUN NADHIROH; WIWIET TEGUH TAUFANI (Society for Indonesian Biodiversity, 2023)
Abstract. Wiadnya DGR, Harlyan LI, Rahman MA, Mustikarani SMI, Nadhiroh ENS, Taufani WT. 2023. Stock status and supporting species of anchovy fisheries in the northern of East Java, Indonesia. Biodiversitas 24: 4775-4782. Anchovy, a commercial fish with high demand in local and international markets, was selected as the Unit of Assessment (UoA) of the Fisheries Improvement Project (FIP) based on the priority fisheries consultation process under the Marine Stewardship Council certification in Indonesia. One of the criteria is the availability of stock status and information about supporting species. This research was conducted from January to May 2022 at Lekok Fishing Port, Pasuruan, and Karangagung Fishing Port, Tuban, using primary data collection methods, including a fishery survey to obtain data species composition data and fishing coordinates. The secondary data were the catch-effort data from 2013 to 2021 collected from both fishing ports. Data analysis was carried out by the surplus production models, Schaefer and Fox model, to determine the total allowable catch (TAC) and the exploitation rates of anchovy fisheries. The participatory mapping method was carried out to obtain data on the distribution of fishing grounds and catch composition. The exploitation rate of anchovy (Stolephorus commersonnii) and large anchovy (Encrasicholina punctifer) landed in the Lekok fishing port was 76% and 75% (moderate), respectively. In this situation, fishing efforts can still be increased, as TAC value for anchovy fisheries' sustainability. On the other hand, the exploitation rate of anchovy in the northern waters of Tuban is 105% (over-exploited), which is necessary to reduce fishing efforts for its sustainability. The classification of supporting species resulted in 19 identified species in the Lekok fishing port, covering three target species: two endangered threatened and protected (ETP) species, two main primary species, six minor primary species, one major secondary species, and five minor secondary species. While in Karangagung fishing port, eight species were identified, consisting of 1 major primary species, five minor primary species, and two minor secondary species. The supporting species' information is required to complete FIP Anchovy fisheries.